The dance of justice: a Rawlsian perspective in Srividya Natarajan’s the undoing dance - Othaya Kumar, Yusintha; Mani, Manimangai (Universiti Putra Malaysia Press, 2024)
This article delves into the role of Bharatanatyam, a classical Indian dance, as a transformative force for Kalyani, the protagonist in the novel The Undoing Dance (2018). It investigates how Bharatanatyam serves not only as a form of artistic expression but also as a means of transcending caste boundaries and societal expectations. By applying the concept of the difference principle, a framework within socio-political theory, the study examines how caste-based discrimination is confronted and reimagined through the medium of dance. Natarajan's narrative, which alternates between past and present, underscores the significance of Bharatanatyam in conveying Kalyani’s inner turmoil, struggles, and ultimate empowerment. Kalyani’s journey is marked by her revaluation of her Devadasi roots—a lineage steeped in both cultural richness and societal stigmatisation. As she reconnects with her heritage, she gains a deeper understanding of the matriarchal traditions within her community and begins to reinterpret them through her dance. This exploration leads to a redefined sense of identity and womanhood, where Bharatanatyam becomes a vessel for Kalyani’s self-expression and liberation. This study argues that classical dance, particularly Bharatanatyam, provides a unique lens through which the complexities of the Indian caste system can be viewed, offering Devadasi women in South India a powerful tool for reclaiming their narratives and challenging the entrenched social hierarchies. Through dance, Kalyani not only reclaims her heritage but also transforms her pain and suffering into a powerful statement of resilience and identity.